Building Harmony through a Local Wisdom-Based Curriculum at a Madrasah in a Muslim Minority Setting - Nadlir Nadlir; Muhammad Fahmi; Hanik Yuni Alfiyah; Syaifuddin Syaifuddin; Ali Mas'ud; Sudirman Sudirman; Abdullah Malik Ibrahim (Nazhruna: Jurnal Pendidikan Islam, 2026)
Interfaith harmony is an important foundation for social cohesion in a pluralistic society, but it does not always occur naturally and requires a planned educational strategy. This study aims to analyze the construction of harmony through a local wisdom-based curriculum at Madrasah Aliyah Bali Bina Insani (MA BBI), a madrasah located in a Muslim minority context in Tabanan Regency, Bali. The research focuses on how local wisdom values ​​are systematically integrated into the curriculum and educational practices to build interfaith harmony. This study used a qualitative case study design. Data were collected through in-depth interviews with eight key informants, including madrasah principals, Muslim and non-Muslim teachers, and community leaders; participant observation of the learning process and socio-religious activities; and documentation of curriculum documents and institutional policies. Data were analyzed using an inductive-interactive analysis model. The results show that MA BBI actively integrates Balinese local wisdom into its learning materials, inclusive pedagogical approaches, and institutional policies, thus creating an educational climate that supports tolerance, mutual respect, and social harmony. The curriculum serves not only as an academic tool but also as a social instrument in building harmony amidst religious diversity. The novelty of this research lies in its emphasis on the madrasah curriculum as a medium for fostering harmony among minority communities. This study confirms that developing a curriculum grounded in local wisdom is a powerful educational strategy for building social harmony in pluralistic societies and recommends further research across diverse socio-cultural contexts.